Night stalkers from above: A monograph of Toxicodryas tree snakes (Squamata: Colubridae) with descriptions of two new cryptic species from Central Africa - Greenbaum, Eli; Allen, Kaitlin E.; Vaughan, Eugene R.; Pauwels, Olivier S. G.; Wallach, Van; Kusamba, Chifundera; Muninga, Wandege M.; Aristote, Mwenebatu M.; Mali, Franck M. M.; Badjedjea, Gabriel; Penner, Johannes; Rödel, Mark-Oliver; et al. (Zootaxa, 2021)
The genus Toxicodryas, historically included with the renowned Australasian cat-eyed snakes of the colubrid genus Boiga, currently includes two widespread species (T. blandingii and T. pulverulenta) in western, central, and eastern Africa. We leverage findings from a recent phylogenomic and historical demographic analysis of this genus (based on 2848–4471 Rad-seq loci from across the genome), with robust sampling from throughout the ranges of both species, to define two additional taxonomic units, with species boundaries corresponding to river barriers. Additional morphometric data from scores of examined museum specimens and literature records bolster the recognition of these two new cryptic species. We hypothesize that T. blandingii occurs west of the confluence of the Congo and Ubangi rivers, whereas a cryptic new species that is found east of this biogeographic barrier has significantly higher numbers of ventral scale counts in both sexes, additional significant differences in several scale counts, and lower venom toxicity. Toxicodryas pulverulenta occurs west of the Niger Delta in West Africa, whereas a cryptic new species that is found east of this biogeographic barrier has significantly higher numbers of subcaudal scale counts in both sexes. A review of published information regarding morphological variation, ecology, natural history, habitat, and venom is summarized for these four Toxicodryas species.